Effect of broadband excitation ions in the luminescence of Ln.³+ doped SrF₂ nanophosphor for solar cell application - Yagoub, Mubarak Yagoub Adam (University of the Free State, 2015)
SrF2:Pr3+-Yb3+ phosphor powder was previously investigated for down-conversion application in solar cells. The rst surface, structural and optical characterization results indicated that the Pr3+-Yb3+ couple requires a sensitizer for effective enhancement in energy conversion. Broadband excitation ions of Ce3+ and Eu2+, that could be used as sensitizers, were therefore doped and co-doped in the SrF2 crystal. Detailed characterizations and investigations were then done on the surface, structure and optical aspects to see the effect on the energy conversion. Initially, the influence of different synthesis techniques on the surface, structure and concentration quenching of Pr3+ doped SrF2 was studied. The singly doped SrF2:Pr3+ was prepared by the hydrothermal and combustion methods. Scanning electron microscope (SEM) images showed different morphologies which was an indication that the morphology of the SrF2:Pr3+ phosphor strongly depended on the synthesis procedure. Both the SrF2:Pr3+ samples exhibited blue-red emission under a 439 nm excitation wavelength at room temperature. The emission intensity of Pr3+ was also found to be dependent on the synthesis procedure. The dipole-dipole interaction was found to be responsible for the concentration quenching effects at high Pr3+ concentration in both methods. SrF2:Eu nano-phosphors were successfully synthesized by the hydrothermal method. The crystalline size of the phosphors was found to be in the nanometre scale. The photoluminescence and high resolution x-ray photoelectron spectroscopy (XPS) results indicated that the Eu was in both Eu2+ and Eu3+ valance states. The presence of Eu2+ and Eu3+ in the system largely enhanced the response of the Eu3+ under ultraviolet excitation. Time of flight secondary ion mass spectrometry (tof-SIMS) results suggested that the energy transfer between these two ions was likely occurred. The relative photoluminescence intensity of the Eu2+ rapidly decreased with an increasing laser beam irradiating time. This result would make the current Eu2+ doped SrF2 samples unsuitable candidates for several applications, such as white light-emitting diodes and wavelength conversion films for silicon photovoltaic cells. The effect of Ce3+ ions on the SrF2:Eu nano-phosphor was also studied. Ce3+ largely enhanced the Eu3+ emission intensity via energy transfer mechanism. The calculated energy transfer efficiency was relatively effcient at high Eu concentration. The results suggested that Ce3+ may therefore be used as an efficient sensitizer to feed the Eu ions in SrF2 host. Eu2+ co-doped Pr3+, Yb3+ and Pr3+-Yb3+ couple in SrF2 were successfully prepared. XPS confirmed that all Eu contents were in Eu2+ oxidation states. Initially, Eu2+ co-doped SrF2:Pr3+ was studied. From PL and decay curve results, an efficient energy transfer was demonstrated in SrF2:Eu2+, Pr3+ phosphors. The energy transfer process was effective until a concentration quenching between Pr3+ ions occurred. The results proposed that Eu2+ could be a good sensitizer for absorbing the UV photons and hence efficiently enhancing the Pr3+ emission intensity. SrF2:Eu2+ (1.5 mol%) co-doped with Na+ (0.5 mol%) and various concentrations of Yb3+ were also investigated. XRD results showed a mixture of the cubic SrF2 and NaYbF4 phases. The NaYbF4 phase gradually formed with increasing Yb3+ doping concentration. Emission spectra and the fluorescence decay curve measurements were utilized to demonstrate the cooperative energy transfer. Energy transfer occurred subsequently from Eu2+ to Yb3+ followed by intense NIR emission. The energy transfer was completed at high concentrations but the Yb3+ emission intensity was reduced as a result of concentration quenching. In addition, from the photoluminescence data it was evident that Na+ induced significant change to NIR emission. The possibility of using the broadband absorption of Eu2+ to sensitize the Pr3+-Yb3+ down-conversion couple in SrF2 matrix was also investigated. The energy transfer process was demonstrated by the decrease of Eu2+ and Pr3+ related photoluminescence and lifetime with increasing Yb3+ concentration. Upon 325 nm excitation into the 5d levels of Eu2+, the samples yield intense near infrared emission corresponding to Pr3+:4f-4f and Yb3+:4f-4f transition. Yb3+ emission was clearly observed only at high Yb3+ concentrations after the emission intensity of Pr3+ was quenched. The PL lifetime results of Eu2+ confirmed the the second-order cooperative energy transfer also occurred between Eu2+ and Yb3+ ions.
Thesis (Ph.D. (Physics))--University of the Free State, 2015
Keywords: Luminescence; Solar cells